Planning energy-water nexus system under multiple uncertainties – A case study of Hebei province - Lv, J.; Li, Y.P.; Shan, B.G.; Jin, S.W.; Suo, C. (Applied energy, 2018)
•An interval-fuzzy chance-constrained programming method is developed.•It can address uncertainties expressed as interval values and fuzzy random variables.•Energy-water nexus system optimization model is formulated for Hebei, China.•Tradeoffs among system cost, electricity demand and water resources are analyzed.•The proportion of coal-fired power would reduce by about 12.09% in 2023. Energy and water are inextricably linked. The shrinking water availabilities, increasing energy demand, and severe resources shortage pose great challenges for socioeconomic sustainable development. In this study, an interval-fuzzy chance-constrained programming method that is capable of addressing uncertainties expressed as interval values, fuzzy sets and fuzzy-probability distributions existed in the energy-water nexus system is developed. Then, the developed method is applied to a real case of Hebei province (in northern China) that heavily relies on fossil fuels such as coal and oil as sources of energy. A variety of scenarios associated with different water availabilities and multiple uncertainties are examined. Results reveal that both water availabilities and uncertainties have significant effects on the energy-water nexus system planning strategies. Compared to the scenario with high water-availability, the energy-water nexus system would save 10.9% of water under low water availability; however, the imported electricity would increase 8.2% to offset the local power-generation shortage. Results also disclose that the study system would gradually transit to renewable energies and the proportion of coal-fired power would reduce by 12.09% at the end of planning horizon. These findings can provide useful information for the other regions to achieve adjustment of the conflict among economic objective, electricity demand, and water shortage.